Risk analysis and assessment for transportation of dangerous freight - Batarlienė, Nijolė (Transport, 2008)
This work examines conditions to ensure safe transportation of dangerous freight, to manage and minimize the risk of carriage of such freight along the whole route. This article presents the probabilities in transport of dangerous freight, probability of possible damage and that of a possible accident, when transporting dangerous freight and a method of calculating costs of damage to the environment and that of calculating accident probability. The article points out the ways of reducing the risk of possible damage and probability of accident. First published online: 27 Oct 2010